INTERACTION BETWEEN JOURNALISTS AND AUDIENCES ON ONLINE PLATFORMS - Tokhirova Sevinch Akram kizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
The development of digital technologies and social media has transformed the relationship between journalists and their audiences. Online platforms enable direct, real-time interaction, breaking the traditional one-way flow of information and fostering a more participatory media environment. This article explores how the interaction between journalists and audiences on digital platforms influences news production, dissemination, credibility, and public engagement. It also examines challenges such as misinformation, audience fragmentation, and ethical considerations in digital communication.